The Chinese inward FDI and economic prospects amid COVID-19 crisis - Ahmet Faruk Aysan; Farrukh Nawaz Kayani; Umar Nawaz Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Novel coronavirus (COVID- 19) is not only a public health threat, but it is also a serious economic threat to the whole world. This article is to analyze economic impact of COVID-19 upon Chinese economy. COVID-19 has plunged the world into deepest recession with unprecedented levels of poverty, deprivation, and unemployment. Some political economists are calling the initial mishandling of COVID- 19 as a monumental failure of Chinese governance and institutions. However, as the time passes by, the Western economies have not done better than China in constraining the pandemic. The COVID-19 has negatively affected the global foreign direct investment (FDI) flows. This article contributes on the possible policy routes for the global economy and for the Chinese economic prospects.
Keywords: 330; Beijing consensus; relocation of FDI; made in China strategy and economic growth